In vitro induction and proliferation of adventitious roots in pineapple (Ananas comosus L.) cultivars of smooth cayenne and morris - Hamad, A.H.M.; Taha, R.M.; Mohajer, S. (2013)
The effect of shoot age (6 and 10-month-old) in quarter, half and full strength of two MS medium types (solid, liquid) supplemented with different concentrations of auxins and cytokinins on two pineapple cultivars (Smooth Cayenne and Morris) were examined to identify the optimal combination for root formation. All the shoots of both cultivars rooted in solid medium enriched with 2.0 mg/L IBA at quarter strength for Smooth Cayenne and half strength for Morris. Full strength solid medium enriched with 1.0 mg/L NAA was the best choice for rooting of both Smooth Cayenne and Morris, resulting in the tallest plantlets (74.1 mm), highest number of roots per shoot (11.4) and intermediate rooting percentage (89.5). Neither shoot ages nor hormone types and concentrations had a significant effect on the rooting percentage. However, the largest number of roots was obtained from 6-month-old shoots treated with 1.0 mg/L NAA. Solid medium could be used to induce 100 rooting and formation of 5 to 7 roots per shoot. In liquid medium, shoots failed to form roots in media containing NAA, while 100 rooting with 4 to 5 roots per shoot were obtained in medium enriched with IAA and IBA.